THE SIGNIFICANCE OF TRADE SECRETS WITHIN THE FRAMEWORK OF CIVIL LAW OBJECTS - Raimova Nargiza Doroyevna (Modern American Journals, 2025)
It is noted in the article that the problems related to the fact that the legislation provides a wide range of powers by government organs in the different tests that may affect the interests of sensitive enterprise because unset concrete facets of government intervention in economic activities of enterprises considered painful for entrepreneurs in many countries. Based on the study of foreign experience and scientific and theoretical views, ways to improve legislation in the field of regulation of confidential information were investigated, relevant conclusions were drawn and proposals were developed for the current legislation.
Keywords: Intellectual property, information, confidential information, legal regime, types of information, methods of protection of information, modern criteria.